Preference shifts and wage inequality. Issue 5 (4th July 2022) - Pi, Jiancai; Huang, Xiangyu
Abstract : This paper analyzes how preference shifts affect wage inequality. We take the Cobb–Douglas preference, the Dixit-Stiglitz preference and the quasi-linear preference into account, and find that there exists preference-driven wage inequality. In the two-type labor (i.e. skilled labor and unskilled labor) models, when the preferences of consumers for skilled products are strengthened, wage inequality will be widened (resp. narrowed down) if there is a relatively low (resp. high) capital intensity in the unskilled sector. We also build a three-type labor (i.e. high-skilled labor, medium-skilled labor, and unskilled labor) model and a model with a non-tradable unskilled sector to strengthen the explanatory power. The role of preferences shifts in changing wage inequality is overlooked by the existing literature.